2016
DOI: 10.1016/j.jvir.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Survey of Interventional Radiologists and Vascular Surgeons Regarding the Cost and Reimbursement of Common Devices and Procedures

Abstract: Purpose To evaluate knowledge of interventional radiologists (IRs) and vascular surgeons (VSs) on the cost of common devices and procedures and to determine factors associated with differences in understanding. Materials and Methods An online survey was administered to US faculty IRs and VSs. Demographic information and physicians’ opinions on hospital costs were elicited. Respondents were asked to estimate the average price of 15 commonly used devices and to estimate the work relative value units (wRVUs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…This includes personnel costs but to the same extent costs for consumables, something many IRs are not aware of. So-called cost-education may raise awareness of this issue and ultimately lead to more cost-effective care [ 50 ]. Especially in larger units, the problem of interfaces plays a key role.…”
Section: Organisation In Irmentioning
confidence: 99%
“…This includes personnel costs but to the same extent costs for consumables, something many IRs are not aware of. So-called cost-education may raise awareness of this issue and ultimately lead to more cost-effective care [ 50 ]. Especially in larger units, the problem of interfaces plays a key role.…”
Section: Organisation In Irmentioning
confidence: 99%
“…Generally, the accuracy of physician estimates obtained in the current study was similar to findings from previous studies that found poor physician awareness of costs related to both pharmaceuticals and nonpharmaceutical diagnostic and therapeutic interventions. 6,7,11,27 Previous research has suggested that surgeons tend to overestimate less expensive, more common surgical equipment and to underestimate the cost of more expensive, less common equipment. 11,28,29 Similarly, we found that surgeons tended to overestimate the total cost of the less expensive open procedure and underestimated the cost of the more expensive laparoscopic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrate that surgeons have not been able to predict cost well, both overestimating and underestimating costs [11,12]. In contrast to predicting the cost of an item, the ability to differentiate a more expensive item of two choices may be a more clinically relevant measure of cost knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently only a handful of studies that assess cost knowledge and decision making in surgery, many of which are limited to surgeons and residents and exclude other members of the surgical team [11][12][13]. In an effort to further elucidate the effect of cost awareness among members of the surgical team, the current study aimed to investigate the perceptions of those at an academic institution about the cost differences and perceived value of commonly used materials and implants that are regularly used for TJA in the operating rooms (ORs) where they work.…”
Section: Introductionmentioning
confidence: 99%